A Preliminary Study on Hepatoprotective, Hypolipidemic and Aortic Morphometric Effects of Omega-3-Rich Fish Oil in Hypercholesterolemic Mice - Ana Lina C. C. Sales; Maísa G. S. Primo; Renato S. Mello Neto; Ana Victória S. Mendes; Mariely M. Furtado; Joana Érica L. Rocha; José Otávio C. S. Almeida; José Vinícius S. França; Salmon R. Alencar; Ana Karolinne S. Brito; Luana O. Lopes; Márcia S. Rizzo; et al. (MDPI AG, 2024)
This study aims to evaluate the hepatoprotective, hypolipidemic and aortic morphometric effects of fish oil rich in omega-3 in hypercholesterolemic BALB/c mice. This is an experimental model that included 16 male BALB/c mice (Mus musculus) divided into three groups (G1 (standard commercial chow and 0.9% saline solution), G2 (hypercholesterolemic diet and 0.9% saline solution) and G3 (hypercholesterolemic diet and fish oil)) for 8 weeks. There was no significant difference in the treatment with omega-3-rich fish oil in the lipid profile (p > 0.05). In the histological analysis, group G2 detected the presence of hepatitis and liver tissue necrosis, but this was not observed in group G3. As for the morphometry in the light area of the vessel, the G1 group had a higher score (2.62 ± 0.36 mm2) when compared to G2 (2.10 ± 0.16 mm2) and G3 (2.26 ± 0.25 mm2) (p < 0.05). The vessel wall thickness did not differ between the groups (p > 0.05). It is concluded that supplementation with fish oil rich in omega-3 carried out in this study may have a protective effect on liver tissue, but it has not yet improved the lipid and morphometric profile. Despite this research being preliminary, it is a relevant study with future prospects for improving the doses of EPA and DHA in order to better elucidate the benefits of fish oil in models of dyslipidemia.